PENGARUH MOTIVASI DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN DI RUMAH SAKIT NUR HIDAYAH BANTUL - Mudayana, Ahmad Ahid (Universitas Ahmad Dahlan, 2010)
Background: : The process of development is a Nur Hidayah Hospital (RS Nur Hidayah) Bantul makes employees work load increases. Improved performance the hospital can improve employee performance. If the employees performance is getting better, the service given to the patients will be getting better too . While the employees performance can be influenced by the work motivation. The researcher interested to do research the influence of motivation on performance of employees. Objective: Measure of motivation and employee performance. Measure the influence of motivation on employee performance. Method: this was quantitatif descriptive research using cross sectional approach plan. the number of 79 employees respondents from 111 employees. The data analyzed using correlation analysis. Motivation assessed by questionnaire, performance while using a checklist. Result and discussion: Motivation (82, 3%) and performance (92, 4 %) employees are included in the high category. There is significant influence between motivation on employee performance (r=0,775 p (0, 00) <0, 05). Influence of intrinsic motivation (r=0,737) more powerful than extrinsic motivation (r=0,325). There is influence of the sub variables of responsibility (p=0,032), recognition (p=0,002), work achievement (p=0,007), career development (p=0,000), work (p=0,016), promotion (p=0,029), work condition (p=0,001) on employee performance. Conclusion and recommendation: This study shows motivation and employee performance is already high. Overall there is a strong influence on employee work motivation Nur Hidayah Hospital Bantul. Work motivation still need to be maintained and improved for the better employee performance. Keywords: Motivation, intrinsic motivation, extrinsic motivation, performance